Transcriptome Analysis Reveals Altered Expression of Memory and Neurotransmission Associated Genes in the REM Sleep Deprived Rat Brain - Narwade, Santosh C.; Mallick, Birendra N.; Deobagkar, Deepti D. (Frontiers in Molecular Neuroscience, 2017)
Sleep disorders are associated with cognitive impairment. Selective rapid eye movement sleep (REMS) deprivation (REMSD) alters several physiological processes and behaviors. By employing NGS platform we carried out transcriptomic analysis in brain samples of control rats and those exposed to REMSD. The expression of genes involved in chromatin assembly, methylation, learning, memory, regulation of synaptic transmission, neuronal plasticity and neurohypophysial hormone synthesis were altered. Increased transcription of BMP4, DBH and ATP1B2 genes after REMSD supports our earlier findings and hypothesis. Alteration in the transcripts encoding histone subtypes and important players in chromatin remodeling was observed. The mRNAs which transcribe neurotransmitters such as OXT, AVP, PMCH and LNPEP and two small non-coding RNAs, namely RMRP and BC1 were down regulated. At least some of these changes are likely to regulate REMS and may participate in the consequences of REMS loss. Thus, the findings of this study have identified key epigenetic regulators and neuronal plasticity genes associated to REMS and its loss. This analysis provides a background and opens up avenues for unraveling their specific roles in the complex behavioral network particularly in relation to sustained REMS-loss associated changes.